The Religious Values in The Novel "99 Lights In The European Sky" by Hanum Salsabiela Rais and Rangga Almahendra - Kasturi, Kasturi; Alfiawati, Riska; Subari, Imam (IJLHE: International Journal of Language, Humanities, and Education, 2021)
This study aimed to analyze the religious values ​​contained in the novel "99 Lights in the Sky Europe" by Hanum Salsabiela rais and Rangga Almahendra. The researchers cite data in the form of words, sentences, paragraphs, and dialogues in the novel, which contains various religious values ​​between humans and their God, religious values ​​between humans and other humans, religious values ​​between humans and themselves, and the relationship between religion and science. The method used in this study uses a qualitative approach with the type of library research, namely by analyzing the data in the form of paragraph sentences or dialogues containing religious values. The researchers hope this novel is helpful for all of us and can be used as a source of inspiration for the nation's young generation to reach a goal without forgetting religious values.